ISO 9001 Quality Certification and Financial Performance of Selected Manufacturing Companies - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 10 No.2, 2011 JBE UNKLAB, 2011)
This study was to fill a significant gap in the research, more specifically to determine the practices of ISO 9001 quality management certification and financial performance.  Cronbach alpha was utilized to measure the reliability of the four scale likert-type questionnaire. Also the annual audited financial records of the 71 food and beverage manufacturing companies in the Philippines were gathered. The results of this study revealed that ISO 9001 certified companies strongly agree to practice ISO 9001 quality management certification than non-ISO certified companies. Leadership, mutual benefit supplier quality management, and continual improvement are the highest among the principles. In terms of level of return on asset (ROA), there is no statistical significant difference between ISO and non-ISO certified companies, and company size.